Advocacy Strategies of Labour Unions in Demanding Workers’ Rights during the COVID-19 Pandemic - Novianto, Imam Satrio (PCD Journal, 2024)
This paper explores the strategies and advocacy steps taken by Serikat Pekerja Sejahtera Mandiri Jogja Bay Waterpark (Spektram JBW) during the COVID-19 pandemic causing 31 relieved of duty workers and 8 laid-off workers. This research uses a qualitative method with a case study approach. Through the analysis of advocacy theory from Sharma (2004) and contentious politics theory from Tarrow (2011), this paper shows that Spektram JBW's advocacy strategy follow five advocacy steps, namely identifying the root of the problem, formulating solutions, building political awareness, policy implementation, and evaluation. The five steps illustrate the process of contentious politics (movement process) with the formation of the union, and the unity of ordinary workers against the corporate elite. The advocacy resulted on two main demands were achieved but demand for worker status failed, and the process continued to the Industrial Relations Court (Pengadilan Hubungan Industrial, or PHI). The success of Spektram JBW is an example of success story providing a bright spot for other unions in Yogyakarta. The failure stems from the union culture in the area of DIY which lacks unions and the small scale of industry which makes it difficult to mobilise large numbers of workers.